Executive equity incentives, employee stock ownership plans, and enterprise performance: Empirical evidence based on environmental uncertainty - Tian, Zhihao (Frontiers in Environmental Science, 2022)
Taking China's A-share listed companies from 2014 to 2021 as the research sample, this paper verifies the differential impact of executive equity incentive and employee stock ownership plan on enterprise performance, and examines the economic consequences of their implementation under the influence of environmental uncertainty, the nature of property rights and the quality of external audit. The results show that: (1) There are significant differences between executive equity incentive and employee stock ownership plan on enterprise performance. (2) The effect of executive equity incentive is more significant when the environmental uncertainty is low, while the effect of employee stock ownership plan is more significant when the environmental uncertainty is high. (3) The equity incentive of state-owned listed companies can not significantly improve enterprise performance when the environmental uncertainty is high. (4) High quality external audit can significantly improve the effect of equity incentive on enterprise performance, and the effect is more obvious when the environmental uncertainty is high. The research conclusion confirms the necessity of reasonably selecting equity incentive objects under the influence of environmental uncertainty, and also provides a useful reference for optimizing the reform of equity incentive system of state-owned enterprises and perfecting the external audit system.